2x + 2x + 146 + 26 = 172 4x + 172 = 172 4x = 0 x = 0
y=4x-8y=2x+10Substitute (4x-8) for y in the second equation and solve for x:4x-8=2x+102x=18x=9Now solve for y:y=4(9)-8=28(9,28)
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
2x+4-x = 4x-5 2x-x-4x = -5-4 -3x = -9 x = 3
many solutions
2x + 2x + 146 + 26 = 172 4x + 172 = 172 4x = 0 x = 0
3x - 5x + 4x = -2x +4x = 2x
4x+2=2x-102x=-12 x=-6
-2x = -4x + 24 -2x + 4x = 24 2x = 24 x = 24/2 x = 12
4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4
2y = 4x + 4y = 2x + 2
y=4x-8y=2x+10Substitute (4x-8) for y in the second equation and solve for x:4x-8=2x+102x=18x=9Now solve for y:y=4(9)-8=28(9,28)
4x-y2=2xy 2x ? y5 if its plus its 7 xy
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
2x+4-x = 4x-5 2x-x-4x = -5-4 -3x = -9 x = 3
many solutions
4x=-10 x=-2.5